Analisis Kepraktisan Lembar Kerja Mahasiswa Menggunakan Pembelajaran Berbasis Proyek Potensi Lokal Moloku Kie Raha pada Matakuliah Kimia Anorganik II - Limatahu, Nur A.; Roini, Chumidach; Limatahu, Iqbal; Ibrahim, Fitriana; Nadut, Anggelinus; Sangadji, Fani Rahmasari (Peneliti.net, 2023)
This research aims to analyze the practicality of Student Worksheets (LKM) using Moloku Kie Raha's local potential project-based learning in the Inorganic Chemistry II course. The research population was 26 students in the fourth semester of the 2022-2023 academic year in the Chemistry Education study program, Mathematics and Natural Sciences Education department, Faculty of Teacher Training and Education, Khairun University. All sample members are used as the population (saturated sample or total sample). Data was obtained through a student response questionnaire during class learning with indicators of the novelty of the material presented, the attractiveness of the LKM display, motivation to learn, the ability to learn more independently, and the ability to learn cooperatively. Data analysis was carried out using a rating scale, transformation of qualitative data into quantitative, and percentages. The research results show that the percentage of practicality of LKM using Moloku Kie Raha local potential project-based learning is 87.2% and is categorized as very practical. The conclusion of this research is that the LKM based on the Moloku Kie Raha local potential project is very practical and suitable for use in Inorganic Chemistry II lectures.